Application of Artificial Intelligence and Blockchain in healthcare management - donor organ transplant system - Swapnil Morande; Marialuisa Marzullo (goodwood publishing)
Purpose: Research ventures to expand the reach of organ transplant mechanisms to improve the abysmally low organ transplant rate in the country. The research deploys state of the art technologies to promote deceased organ donation using the donor organ transplant system. Research methodology: The exploratory study focuses on addressing the limitation of resources using a Socio-material view. The research utilizes qualitative content analysis to reflect on the knowledge drawn from the artifacts. Results: The presented study leverages the capabilities of Artificial Intelligence and Blockchain technologies to benefit from the convergence. In line with the concept of 'Texture of Practices,' research provides recommendations to augment the organ transplant system in terms of procurement, coordination, and transplantation. Limitations: Drawing the knowledge from the case studies, research strives to understand the reality and interaction of actors in a healthcare context. Considering the complex nature of the organ transplant process, the study is limited to the Indian scenario and cannot be generalized. Contribution: Research identifies the requirement of a unified digital interface and encourages the integration of emergency health services to facilitate operational processes during organ transplants. Keywords: Healthcare, Organ transplant, A.I., Blockchain, Texture of practices